Pitfalls ; Living dangerously; Ang tunay na Amo - Lazaro, Cheche (The Probe Team, 1991)
Focuses on the violations of benguet Corporation in the reidents property and ecological rights; accidents in building constructions and factories and the Amo Band composed of young uncharacteristic band members who don't smoke, drink or take drugs but just play music for people who are fanatics to their music.